PENGARUH PEMAKAIAN BENGKUNG TERHADAP INVOLUSI UTERUS PADA IBU NIFAS DIWILAYAH KERJA PUSKESMAS SIAK HULU II - Siti Qomariah; Sara Herlina; Wiwi Sartika (LPPM Universitas Abdurrab, 2024)
During the postpartum period, changes occur in the reproductive organs, including the uterus, cervix, vagina, perineum and pelvic organ muscles. In the uterus, several changes occur starting from uterine involution, contractions, afterpains, regeneration of the placenta and expulsion of the lochea from the birth canal. During the postpartum period, the process of uterine involution will take place, the process of shrinking the uterus until it returns to its original size or before pregnancy. Normally after the tenth day the uterus is no longer palpable, but if up to 2 weeks after delivery the uterus has not yet entered the pelvis, subinvolution should be suspected. The use of bengkung is considered to provide many benefits for the recovery process of postpartum mothers by the community. Traditionally, the use of bengkung (stagen) can slim down a stretched stomach, especially for women after giving birth. This is due to pressure in the abdominal cavity so that it can help the uterus contract to its original shape. The aim of this study was to determine the effect of using bengkung on uterine involution in postpartum mothers. This research uses a preexperimental research design with a one group pretest and posttest research approach. The sample in this study consisted of 15 postpartum mothers. The data analysis used was univariate and bivariate using the Wilcoxon pretest-posttest test. The results of data analysis obtained a p-value of 0.001 (p < 0.05) which indicates that Ha is accepted. Thus, it can be concluded that there is an influence of the use of bengkung on uterine involution in the working area of ​​the Siak Hulu II Kampar Community Health Center. It is recommended for mothers to use bengkung as a process to tighten the abdominal muscles and help speed up the recovery of the uterus to its original shape